Engineering Yarrowia lipolytica to Produce Itaconic Acid From Waste Cooking Oil - Rong, Lanxin; Miao, Lin; Wang, Shuhui; Wang, Yaping; Liu, Shiqi; Lu, Zhihui; Zhao, Baixiang; Zhang, Cuiying; Xiao, Dongguang; Pushpanathan, Krithi; Wong, Adison; Yu, Aiqun (Frontiers in Bioengineering and Biotechnology, 2022)
Itaconic acid (IA) is a high-value organic acid with a plethora of industrial applications. In this study, we seek to develop a microbial cell factory that could utilize waste cooking oil (WCO) as raw material for circular and cost-effective production of the abovementioned biochemical. Specifically, we expressed cis-aconitic acid decarboxylase (CAD) gene from Aspergillus terreus in either the cytosol or peroxisome of Yarrowia lipolytica and assayed for production of IA on WCO. To further improve production yield, the 10 genes involved in the production pathway of acetyl-CoA, an intermediate metabolite necessary for the synthesis of cis-aconitic acid, were individually overexpressed and investigated for their impact on IA production. To minimize off-target flux channeling, we had also knocked out genes related to competing pathways in the peroxisome. Impressively, IA titer up to 54.55 g/L was achieved in our engineered Y. lipolytica in a 5 L bioreactor using WCO as the sole carbon source.